Beiträge zur Kenntnis mitteleuropäischer Wanzen (Heteroptera). - Polentz, Georg (Contributions to Entomology = Beiträge zur Entomologie, 1959)
There are reported species and formae rare of new to some German districts (Westphalia, Harz Mountains, Saxony). The description of Tinicephalus brevipes E. Wagner v. nigrosignatus Pol. is completed after recent discoveries. 2 per cent, of the specimens of Catoplatus carthusianus Gz. have black pronota. Records on host plants are given in Orthotylus interpositus K. Schm., Blepharidopterus brevicornis E. Wagn., and Conostethus roseus Fall.